2019
DOI: 10.1038/s41377-019-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Satellite UV-Vis spectroscopy: implications for air quality trends and their driving forces in China during 2005–2017

Abstract: Abundances of a range of air pollutants can be inferred from satellite UV-Vis spectroscopy measurements by using the unique absorption signatures of gas species. Here, we implemented several spectral fitting methods to retrieve tropospheric NO2, SO2, and HCHO from the ozone monitoring instrument (OMI), with radiative simulations providing necessary information on the interactions of scattered solar light within the atmosphere. We analyzed the spatial distribution and temporal trends of satellite-observed air p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 47 publications
4
64
0
Order By: Relevance
“…For fire-affected measurements, the slope HCN / CO, defined as the enhancement ratio (EnhR HCN ), is an effective quantity to identify biomass burning emissions (Holzinger et al, 1999;Lutsch et al, 2016;Rinsland et al, 2002;Viatte et al, 2015;Vigouroux et al, 2012;Zhao et al, 2000). Depending on the burned biomaterials, fire type, the phase of the fire, and the travel time of the plumes, the reported EnhR HCN varied by 2 orders of magnitude.…”
Section: Correlation With Co and Enhancement Ratiosmentioning
confidence: 99%
“…For fire-affected measurements, the slope HCN / CO, defined as the enhancement ratio (EnhR HCN ), is an effective quantity to identify biomass burning emissions (Holzinger et al, 1999;Lutsch et al, 2016;Rinsland et al, 2002;Viatte et al, 2015;Vigouroux et al, 2012;Zhao et al, 2000). Depending on the burned biomaterials, fire type, the phase of the fire, and the travel time of the plumes, the reported EnhR HCN varied by 2 orders of magnitude.…”
Section: Correlation With Co and Enhancement Ratiosmentioning
confidence: 99%
“…They found that the stagnant weather condition with southerly and westerly winds would worsen the air quality in the North China Plain, and the occurrence of stagnant conditions was relevant to the inter-annual and inter-decadal variability of monsoon. The regional transport of pollutants induced by the large-scale synoptic condition is critical to the air quality (Zhang et al, 2019). Although previous studies have recognized the importance of synoptic pattern and PBL meteorology for the aerosol pollution in BTH, most of them focused on the short-term episodes or a specific city (e.g., Miao et al, 2019b;Quan et al, 2013;Tie et al, 2015;Wang et al, 2019;Zhong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that these type of strong spatial heterogeneity scenarios have been observed in different areas of the planet and specific studies of atmospheric constituents have been or are currently being performed in other urbanized and densely populated areas such as North America (Boeke et al, 2011;Chance et al, 2000;Millet et al, 2008), China (Cheng et al, 2015;Zhang et al, 2019), particularly in the Beijing-Tianjin-Hebei region (Zhu et al, 2018) and the Yangtze River Delta area (Chan et al, 2019;Hong et al, 2018;Tian et al, 2018;Wang et al, 2016); South Asia (Rana et al, 2019) and more specifically India (Chutia et al, 2019;Surl et al, 2018) and Pakistan (Khan et al, 2018;Khokhar et al, 2015). In addition specific case studies have been conducted globally (Wittrock et al, 2006) or in the Southern Hemisphere (Ahn et al, 2019), the Atlantic Ocean (Behrens et al, 2019) and the East China Sea (Tan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%